دراسة عوامل انهيار منظومة البكرة في روافع Takraf العاملة في الشركة العامة لمرفأ اللاذقية وامكانية تحسين أدائها - سلامة أحمد; جعبري راما (Latakia University Journal -Engineering Sciences Series, 2018)
In this paper, we study the causes of the collapse of the pulley system (pulley-bearing- rope) in the electric Takraf crane, statistically and dynamically. Statistical study showed the effect of load factors on various designs of the pulley (basic, basic with increasing number of nerves or strengthening nerves, locally cast ...), the breakdown factors of the pulley system are not due to the loading or the type of metal. All the above cases of the system showed the ability to withstand the maximum load designed on its basis, where the stress value did not exceed the point of the yield stress metal. Therefore, a dynamic study was carried out that took into account the effect of angular velocity on the forces of sliding and dynamic load corresponding to it, and thus on the thickness of lubrication layer in the bearing. تم في هذا البحث دراسة أسباب انهيار منظومة البكرة (بكرة – محمل – حبل) في الرافعة الكهربائية Takraf ستاتيكياً وديناميكياً. حيث بينت الدراسة الستاتيكية لتأثير عوامل التحميل على تصاميم مختلفة للبكرة (الأساسية، الأساسية مع زيادة عدد الأعصاب أو تدعيم الأعصاب، والمصبوبة محلياً ...) أن عوامل انهيار منظومة البكرة لا تتم بسبب التحميل أو نوع المعدن. أوضحت جميع الحالات المدروسة ستاتيكياً للمنظومة قدرتها على تحمل الحمولة الأعظمية المصممة على أساسها، ولم تتجاوز قيمة الاجهاد حد الخضوع للمعدن. لذلك تم إجراء دراسة ديناميكية أخذت بعين الاعتبار تأثير السرعة الزاوية على قوى الانزلاق والحمل الديناميكي المقابل لها، وبالتالي على سماكة طبقة التزييت في المحمل.